Emerging Technologies, Existing Power Structures and the Future - Somwanshi, Gaurav (Prabuddha: Journal of Social Equality; Vol 3 No 1 (2019): Has capitalism destroyed Caste and Race; does capitalism equalize or perpetuate age-old inequalities?, 2019)
Any exploitative socio-economic system has to necessarily rely on myths and propaganda for its existence, and it sustains itself by wielding the power to twist and mutate any new phenomenon, change, or revolt to suit its purpose. Racism does this by deploying tactics of racialization, or as Ta-Nahisi Coates put it, race is the child of racism, not the father, and this distinction is purposefully blurred. The caste system in the Indian subcontinent relies on reification methods, by glorifying some groups and denigrating the rest, to the extent of defining different biologies. Capitalism relies on myths of meritocracy and a misplaced sense of individualism, among such tropes. This article seeks to explore ways through which the emerging technologies such as artificial intelligence, big data, Blockchain and others interact with these existing structures. It will seek to understand the following issues: how much of the interaction results in disruption or dismantling of old ways, how much of it results in the fortification of exploitative structures, and whether some of them are all too new to be judged as of now.